Epidemiology of injuries due to ankle sprain diagnosed in an orthopedic emergency room - Debieux,Pedro (2020)
ABSTRACT Objective To use magnetic resonance imaging to assess the prevalence of foot and ankle ligament injuries and fractures associated with ankle sprain and not diagnosed by x-ray. Methods We included 180 consecutive patients with a history of ankle sprain, assessed at a primary care service in a 12-month period. Magnetic resonance imaging findings were recorded and described. Results Approximately 92% of patients had some type of injury shown on the magnetic resonance imaging. We found 379 ligament injuries, 9 osteochondral injuries, 19 tendinous injuries and 51 fractures. Only 14 magnetic resonance imaging tests (7.8%) did not show any sort of injury. We observed a positive relation between injuries of the lateral complex, syndesmosis and medial ligaments. However, there was a negative correlation between ankle ligament injuries and midfoot injuries. Conclusion There was a high rate of injuries secondary to ankle sprains. We found correlation between lateral ligament injuries and syndesmosis and deltoid injuries. We did not observe a relation between deltoid and syndesmosis injuries or between lateral ligamentous and subtalar injuries. Similarly, no relation was found between ankle and midfoot injuries.